THE MUSHAF BAITURRAHMAN COD.OR.2064: HISTORICAL STUDIES AND ILLUMINATION - Yuni Pamila Sari; Fauziah Nurdin; Reza Idria (Indonesian Journal of Islamic History and Culture, 2021)
"Mushaf Baiturrahman Cod.Or.2064 (Historical Studies and Illumination)" is the title of this study. The declaration of the Dutch war against Aceh in 1873 had an impact on the people of Aceh, since it resulted in the deaths of Acehnese combatants and academics, as well as the destruction of evidence of Acehnese civilisation. One of these was the burning of the Baiturrahman Grand Mosque, which resulted in the scorching and loss of numerous manuscripts and manuscripts, some of which were even transported back to their homelands by foreign invaders. The Baiturrahman Mushaf is one of the manuscripts, and it is presently in the collection of Leiden University with the designation Cod.Or. 2064. The issue in this research is how the historical worth and illumination of the manuscripts are preserved. The aim of the article is to determine the historical significance of the Baiturrahman Cod.Or Mushaf. 2064, as well as the manuscript's existence at Leiden University. In addition, the goal of this work is to examine how the themes in the text illuminations are used. This is a qualitative study that employs library research data gathering methods, observations, and documentation, as well as descriptive analysis to examine data. According to the study, the Baiturrahman Cod.Or.2064 Mushaf was a manuscript discovered by JHA Ijseel de Schepper, a commander of the Dutch army, beside the body of an imam of the Baiturrahman Grand Mosque during the first Dutch military invasion in Aceh in 1873. This document has now been added to the library collection at Leiden University. The illumination in the Baiturrahman Cod.Or.2064 Mushaf may be found at the beginning, middle, and end of the Mushaf. This mushaf illumination motif, in general, follows the same patterns as other Acehnese manuscript illuminations, such as being square with a little "wing" form on the side. Bungong Pucuk Rebung, Lampu Gantung, Bungong Seuleupok, Bungong Tabu, Bungong Puta Taloe, Bungong Sagoe, Bungong Seumanga, Sulur Bunga Daun, Talo Ie, Sulur Bayung, Dada Limpeun, and Madu Sarang are some of the illumination patterns found on the Baiturrahman Cod.Or.2064 Mushaf.